Comparative Analysis of Serum Leptin and Adiponectin Levels in Obese and Non-Obese Individuals and their Association with Cardiovascular Risk - Omer Aslam, Muhammad; Anwar, Ayesha; Abid, Ammara; Akram, Sana; Ullah Khan, Wajahat; Bashir, Zahira (Journal of Neonatal Surgery, 2025)
Background: Obesity is a major global health concern strongly associated with cardiovascular diseases (CVD). Adipokines, particularly leptin and adiponectin, play crucial roles in energy homeostasis, inflammation, and vascular function. Alterations in these biomarkers may contribute to increased cardiovascular risk. Objective: To compare serum leptin and adiponectin levels in obese and non-obese individuals and evaluate their association with cardiovascular risk factors. Methods: A comparative cross-sectional study was conducted on 120 participants (60 obese, 60 non-obese). Serum leptin and adiponectin were measured by ELISA. Cardiovascular parameters were assessed and analyzed using SPSS. Results: Mean serum leptin levels were significantly higher in obese individuals (32.8 ± 8.6 ng/mL) compared to non-obese (11.4 ± 4.2 ng/mL; p<0.001). Mean adiponectin levels were significantly lower in obese individuals (4.6 ± 1.5 µg/mL) compared to non-obese (9.8 ± 2.7 µg/mL; p<0.001). Obese participants had higher BMI (31.9 ± 2.8 vs 22.6 ± 1.9 kg/m²), systolic BP (138.5 ± 12.4 vs 118.2 ± 9.6 mmHg), and LDL levels (142.6 ± 28.3 vs 104.7 ± 22.5 mg/dL). Leptin showed strong positive correlation with BMI (r=0.72) and LDL (r=0.61), while adiponectin showed negative correlation with BMI (r=−0.68) and positive correlation with HDL (r=0.55) (p<0.001). Conclusion: Elevated leptin and reduced adiponectin are significantly associated with increased cardiovascular risk in obese individuals..